ARE CONVENTIONAL RURAL BANKS MORE EFFICIENT THAN SHARIA: EMPIRICAL EVIDENCE FROM DEA - Azhari Azhari; Kamaruddin Kamaruddin; Irvan Murizal; Mai Simahatie (Universitas Padjadjaran, 2022)
This study examined and compared the efficiency level of conventional and Islamic rural banks. The analytical tool used was data envelopment analysis with the variable return scale approach. Furthermore, the input variables consist of total assets, third party funds, and costs. Meanwhile, the total financing and profit are the output variables from 2012 to 2019 for 15 rural banks in Aceh. The results showed conventional rural banks are more efficient than sharia. Therefore, Sharia banks need to engage in better socialization to the public. This is because 2021 is the beginning of qanun (law) of Islamic financial institutions enactment, which obliges change in shape to the sharia pattern. Also, universities are expected to open a study program on sharia bank as a rudiment for human resources in the future. Therefore, the study to compare conventional and sharia rural bank per province in Indonesia is important.